AB0260 Multimorbidity in Rheumatoid Arthritis Patients: Importance of Renal Functional Condition. (15th July 2016) - Zakharova, A.Y.; Gordeev, A.V.; Galushko, E.A.; Nasonov, E.L.
Abstract : Background: RA pts commonly present with multiple concurrent chronic disease, compromising pts quality of life, limiting the use of potential therapies, contributing into disability, rate and costs of hospitalization [1–3]. Objectives: To identify the prevalence and extent of multi-morbid background in RA pts (ACR 1987 y) and relate pts multimorbidity status with RA activity and duration. Methods: 209 RA pts (F-70, 6%, mean age 67, 0±11, 3y), admitted to rheumatology division, were included into analysis. RA duration was 20 [6;109] mo, average disease activity (DAS28) - 5, 2±1, 7, radiographic stage 1–2 was identified in 54, 5% (n=114) pts using the Steinbrocker scoring system. The severity of multimorbid environment was rated using Charlson Comorbidity Index (CCI) and Cumulative Illness Rating Score (CIRS). CCI was calculated using the rating scale with 19 nosological entities, ICD-10 (0–36); CIRS was calculated using the 5 score scale (0–4) to assess 14 major organ systems of the body (0–56). Values of CCI>5 and CIRS>4 were considered as important clinical and prognostic factors in RA pts. Results: Mean CIRS value in RA pts was 15 [10;19] scores, and CCI value - 7 [4;10] scores. There was an obvious correlation between the two indices (r=0, 86, p =0, 005). CIRS and CCI values were independent of the RA duration (r=-0, 43, p =0, 53; r=-0, 12, p =0, 82, respectively) and RA activity (r=-0, 12, p =0, 08; r=0, 02, p =0, 7). The strongest correlation of the two indices was found with eGFR (using CKD-EPI formula), (CIRS r= -0, 61, CCI r= -0, 49; p <0, 01), and with age (r=0, 57, r=0, 49; p <0, 05). CIRS and CCI values also correlated ( p <0, 05) with MAP (mean arterial pressure) (r=0, 48; r=0, 37), excess body weight (r=0, 28; r=0, 35), creatinine levels (r=0, 44, r=0, 39), uric acid levels (r=0, 32, r=0, 31), as well as with hemoglobin level (r=-0, 28, r=-0, 25) and HAQ scores (r=0, 31; r=0, 32). No correlation was found between CIRS and gender, VAS score, and ESR, CRP, cholesterol and liver transaminases levels ( p >0, 05). Conclusions: High multimorbid burden was established in the absolute majority of RA pts. RA duration and activity had no impact on the level of multimorbid burden, measured with CCI and CIRS indices (objective measure of cumulative physical illness burden). Compromised renal function, apart from the age, is of dominant importance in pts management issues, limiting the range of available effective therapies, thus, aggravating RA natural course on one side, and inducing and catalyzing the severity of dysmetabolic syndrome, AH and anemia – on the other. References: JC Peterson, SA Paget, MS Lachs, MC Reid, ME Charlson: The risk of comorbidity/Ann Rheum Dis 2012;71:635–637. B.R. England, H. Sayles, T.R. Mikuls et al.: Validation of the Rheumatic Disease Comorbidity Index/Arthritis Care & Research DOI 10.1002/acr. 22456, 2015 Radner H, Yoshida K, Smolen JS, Solomon DH: Multimorbidity and rheumatic conditions-enhancing the concept of comorbidity. NatRevRheumatol.2014 Apr;10(4):252–6 Disclosure of Interest: None declared